Peningkatan Kualitas Janggel Jagung Sebagai Pakan Sapi Induk Bunting Melalui Proses Amoniasi-Fermentasi (Amofer) - Nandari Dyah Suretno; Fauziah Yulia Adriyani; Reli Hevrizen; Andi Maryanto (Universitas Muhammadiyah Purworejo, 2021)
Self-sufficiency feed for livestock could be achieved by optimizing the use of local resources and the participation all actors including the community. The local resource that can be utilized to support the increase in the cattle population in Lampung Province is the utilization of agricultural waste. Based on this, the purpose of this study is to improve the quality of corn cob as an agricultural waste through the ammonia-fermentation (amofer) process as feed for pregnant cows. The material used was 10 pregnant cows. Observed variables were characteristics of farmers, average daily gain (ADG), and type of feed that was given. The data was analyzed descriptively. The results showed that the average age of farmers was 44 years, which means the farmers is in the productive age. The average of farmers has graduated from elementary school and some have had junior high school education. The feed that was given by farmers who added amofer corn cob are field grass, elephant grass and dwarf grass. Whereas farmers who did not use amofer corn cob have a higher diversity of feed types. The average daily gain (ADG) of cattle that was feed by adding the amofer corn cob when adaptation and treatment are 0.79 kg and 0,26 kg, while those not added are 0.54 kg and 0,23 kg.